Caracterização ecofisiológica de sementes de espécies lenhosas da Caatinga - Sousa, Emerson de Medeiros (2013)
Dormancy is an inherent property of the seeds that define the environmental conditions in which they are able to germinate and their presence is an adaptive trait common in species inhabiting semiarid regions. Moreover, the ability of seedling establishment in these environments has been related to the size, strength and chemical characteristics of the seeds. This study investigated patterns of dormancy and germination speed in tree species of the Caatinga, exploring how the seed size influence the processes of germination, seedling size and biomass allocation. In addition, we aim to investigate the chemical characteristics of the reserves, to verify a possible relationship between nutritional content and the process of seed germination. Therefore, seeds were collected from ten species of woody Caatinga for tests of breaking dormancy, germination and biochemical characterization. Overall, the results show that the scarification treatments mechanical and chemical, and thermal shock influenced the percentage and speed of germination in 50 % of the species, suggesting that they have some level of physical dormancy in the seeds. Biochemical characterization showed the existence of large amounts of carbohydrates in the seeds of all species, low proportion of protein and low amounts of neutral lipids. Using linear regression, we demonstrated the existence of a significant relationship between seed size and the ratio of root/shoot where the largest seeds invested a greater amount of resources for shoot growth. The relationship between germination speed and non-reducing sugar content was also significant, so these compounds is related to the maintenance of physiological seed quality. These results confirm some relationships discussed in the literature for cultivated species, but can be applied to the species native to the Caatinga